Lymph Node Metastasis and Extrathyroidal Extension in Papillary Thyroid Microcarcinoma in Cyprus: Suspicious Subcentimeter Nodules Should Undergo FNA When Multifocality is Suspected. (24th March 2020) - Papaioannou, Christos; Lamnisos, Demetris; Kyriacou, Katerina; Lyssiotis, Theodoros; Constantinides, Vasilis; Frangos, Savvas; Economides, Aliki; Economides, Panayiotis A.
Abstract : Objective . To determine the prevalence of lymph node (LN) metastasis and extrathyroidal extension (ETE) in patients with papillary thyroid microcarcinoma (PTMC) in Cyprus and to evaluate the role of preoperative ultrasound (U/S) examination. Methods . A retrospective study of 102 patients who underwent thyroidectomy for PTMC in a 2-year period. Preoperatively, all patients had a thyroid and neck U/S examination with LN mapping. Tumor size according to the largest diameter, number of foci, LN metastasis, and ETE data was collected from the histopathological report and was compared to the preoperative U/S reports. Results . LN metastasis was present in 23.5% of patients. 15.7% had central, 3.9% had lateral, and 3.9% had both central and lateral LN metastasis. ETE was present in 27.5% of patients. 21.6% had multifocal disease, and in this group, 40.9% had LN metastasis and 36.4% had ETE. Multifocality (p = 0.03 ), size of tumor (p = 0.05 ), and ETE (p ≤ 0.001 ) were significantly associated with LN metastasis. The prevalence of LN metastasis in multifocal PTMC ≤5 mm was the same with multifocal PTMC >5 mm. The preoperative U/S sensitivity for the suspicious lateral neck and central LN was 100%, and the specificity was 100%. The preoperative U/S sensitivity for nodules suspicious for ETE was 53.6%, and the specificity was 100%. Conclusion . The presence of LN metastasis and ETE in our PTMC patients in Cyprus is frequent. Neck U/S mapping is a highly reliable and accurate tool in identifying metastatic nodes. LN metastasis is associated with ETE and multifocality. Suspicious subcentimeter nodules should undergo FNA irrespective of size when multifocality is suspected.